2002
DOI: 10.1074/jbc.m107289200
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Mutational Analysis of the γ Gene fromAzotobacter vinelandii Defines a New Family of Proteins Capable of Metallocluster Binding and Protein Stabilization

Abstract: Dinitrogenase is a heterotetrameric (␣ 2 ␤ 2 ) enzyme that catalyzes the reduction of dinitrogen to ammonium and contains the iron-molybdenum cofactor (FeMo-co) at its active site. Certain Azotobacter vinelandii mutant strains unable to synthesize FeMo-co accumulate an apo form of dinitrogenase (lacking FeMo-co), with a subunit composition ␣ 2 ␤ 2 ␥ 2 , which can be activated in vitro by the addition of FeMo-co. The ␥ protein is able to bind FeMo-co or apodinitrogenase independently, leading to the suggestion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(103 citation statements)
references
References 38 publications
3
98
1
1
Order By: Relevance
“…This observation, in combination with results from quantitative analysis of the SDS͞PAGE and N-terminal amino acid sequencing (data not shown), indicates a subunit composition of ␣ 2 ␤ 2 for ⌬nifH Av1Ј and ␣␤ 2 k for ⌬nifB Av1 V (Table 2). Additional small subunits, encoded by nafY and vnfG, have been reported to be associated with various species of Av1 and Av1 V , respectively (23,27,45,46). However, no additional subunits are detectable in ⌬nifH Av1Ј or ⌬nifB Av1 V based on SDS͞PAGE (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…This observation, in combination with results from quantitative analysis of the SDS͞PAGE and N-terminal amino acid sequencing (data not shown), indicates a subunit composition of ␣ 2 ␤ 2 for ⌬nifH Av1Ј and ␣␤ 2 k for ⌬nifB Av1 V (Table 2). Additional small subunits, encoded by nafY and vnfG, have been reported to be associated with various species of Av1 and Av1 V , respectively (23,27,45,46). However, no additional subunits are detectable in ⌬nifH Av1Ј or ⌬nifB Av1 V based on SDS͞PAGE (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Homer et al (30) have shown that NafY binds FeMo-co specifically and have postulated a role for NafY in the cofactor insertion process. However, Rubio et al (22) have shown that nafY mutants exhibit a nif phenotype only under stress conditions. One interpretation of their data is that NafY is required for the stability of apodinitrogenase in an open conformation that is favorable to the insertion of FeMo-co.…”
Section: Incorporation Of 99 Mo Into Components Of the In Vitro Femo-mentioning
confidence: 99%
“…al in 2002 [25] . The A. vinelandii NafY protein (nitrogenase accessory factor Y, also known as γ  , was reported to be a molecular chaperone that assisted in maintaining the apodinitrogenase in a conformation that facilitated the insertion of the FeMoco by acting as a metalloinsertase [25] .…”
Section: Interaction Of Nafy With Nifxmentioning
confidence: 99%
“…The A. vinelandii NafY protein (nitrogenase accessory factor Y, also known as γ  , was reported to be a molecular chaperone that assisted in maintaining the apodinitrogenase in a conformation that facilitated the insertion of the FeMoco by acting as a metalloinsertase [25] . Mutational analysis of the strains containing mutations in both nafY and nifX showed that these were severely affected in diazotrophic growth, indicating their physiological importance in the stabilization of the apodinitrogenase [25] . Subsequently, the 3-dimensional structure of the NafY protein from A. vinelandii revealed two distinct domains of this protein:…”
Section: Interaction Of Nafy With Nifxmentioning
confidence: 99%
See 1 more Smart Citation